Development of Problem Based Learning (PBL) Teaching Modules To Improve Students' Problem Solving Abilities In Social Science Subjects in Class V Elementary School. IT Ar-Ridha - Yulia Safitri; Diani Syahfiri; Zaifatur Ridha (Alifbata : Jurnal Pendidikan Dasar, 2026)
This study aims to develop a teaching module based on Problem Based Learning (PBL) to improve students' problem-solving skills in IPAS subjects in grade V of SD.it Ar-Ridha. This study used the Research and Development (RnD) method with the ADDIE development model, namely Analyze, Design, Development, Implementation, and Evaluation. The subjects of this study were 25 fifth-grade students and their homeroom teachers. The instruments used included expert validation sheets, practicality questionnaires, and effectiveness tests (pre-test and post-test). Based on the research results, the developed module received an average score of 82.9% from the validators, so the module was categorized as highly valid. The product's practicality test was conducted by teachers and students with an average result of 98.3% and was categorized as very practical. Based on the effectiveness test results using the N-gain score test with a result of 0.8, it was categorized as high. Based on these research results, it can be concluded that the IPAS teaching module based on Problem-Based Learning (PBL) that was developed is valid, practical, and effective for use in the learning process.